2016
DOI: 10.1097/md.0000000000003872
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence, awareness, and treatment of anemia in Chinese patients with nondialysis chronic kidney disease

Abstract: This was the first multicenter, cross-sectional survey to assess the prevalence of anemia, patient awareness, and treatment status in China. Data of patients with chronic kidney disease (CKD; age, 18–75 years; both out- and inpatients) from 25 hospitals in Shanghai, seeking medical treatment at the nephrology department, were collected between July 1, 2012 and August 31, 2012. The prevalence, awareness, and treatment of anemia in patients with nondialysis CKD (ND-CKD) were assessed. Anemia was defined as serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 43 publications
6
82
0
3
Order By: Relevance
“…A similar effect was observed in large‐scale, cross‐sectional, US multicenter survey, where the prevalence was found to be increased with the decline in renal function . Evidence from Chinese cross‐sectional study also reported the similar observation, the prevalence of anemia increased from 22.4 to 79.2% from stage‐I CKD to Stage‐IV CKD . Likewise, Loutradis conducted a nested case‐control study and found a higher prevalence of anemia in T2DM CKD patients with advanced CKD stages .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A similar effect was observed in large‐scale, cross‐sectional, US multicenter survey, where the prevalence was found to be increased with the decline in renal function . Evidence from Chinese cross‐sectional study also reported the similar observation, the prevalence of anemia increased from 22.4 to 79.2% from stage‐I CKD to Stage‐IV CKD . Likewise, Loutradis conducted a nested case‐control study and found a higher prevalence of anemia in T2DM CKD patients with advanced CKD stages .…”
Section: Discussionsupporting
confidence: 66%
“…The reason for the higher prevalence could be the older age of the participants as age is the risk factor for the development of anemia . A multicentre cross‐sectional study from Barcelona and China also reported a high prevalence of anemia (58.5 and 51.5%) in patients with nondialysis CKD . Studies from Korea (44.9%), Cameroon (41.4%), Iran (30%), and United States (15.4%) reported a lower prevalence of anemia person with diabetes with altered kidney function .…”
Section: Discussionmentioning
confidence: 99%
“…The similar Chinese cohort including 2,420 CKD stage 1–5 patients aged 18–75 reported that 51.5% of patients had anemia (9). A Japanese cohort study showed that 32.3% of 2,930 patients with CKD stage 3–5 were diagnosed as anemia (16).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there have been no studies suggesting the target ferritin level in patients with CKD stage 1–2. We used the cutoff value of ferritin at 100 ng/mL and TSAT at 20.0% in accordance with similar studies including patients with CKD stage 1–5 (925). Among patients with anemia, 44.3% had TSAT more than 20.0% and ferritin more than 100 ng/mL in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation